2017
DOI: 10.1002/2211-5463.12347
|View full text |Cite
|
Sign up to set email alerts
|

BMP3 expression by osteoblast lineage cells is regulated by canonical Wnt signaling

Abstract: Bone morphogenetic protein (BMP) and canonical Wnt (cWnt) signaling factors are both known to regulate bone mass, fracture risk, fracture repair, and osteoblastogenesis. BMP3 is the most abundant BMP and negatively regulates osteoblastogenesis and bone mass. Thus, identifying the mechanism by which BMP3 acts to depress bone formation may allow for the development of new therapeutics useful in the treatment for osteopenia and osteoporosis. Here, we report that cWnt signaling stimulates BMP3 expression in osteob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…For example, SNP rs2236373 is associated with gene expression of BMP3 (p = 3.45310 À6 ) and DNA methylation at CpG site Chr16:75279661 (p = 4.42310 À5 ) in BCAR1 gene. Interestingly, both biomarkers were reported to be associated with bone-related signaling pathways, such as WNT pathway (Kokabu and Rosen, 2018) and RANK/RANKL pathway (Robinson et al, 2009). Similarly, we identified 451 SNP-DEG-DMP combinations and 148 SNP-DMC-DMP combinations (Table S7).…”
Section: Targeted Eqtl Meqtl and Metaqtl Analysesmentioning
confidence: 76%
“…For example, SNP rs2236373 is associated with gene expression of BMP3 (p = 3.45310 À6 ) and DNA methylation at CpG site Chr16:75279661 (p = 4.42310 À5 ) in BCAR1 gene. Interestingly, both biomarkers were reported to be associated with bone-related signaling pathways, such as WNT pathway (Kokabu and Rosen, 2018) and RANK/RANKL pathway (Robinson et al, 2009). Similarly, we identified 451 SNP-DEG-DMP combinations and 148 SNP-DMC-DMP combinations (Table S7).…”
Section: Targeted Eqtl Meqtl and Metaqtl Analysesmentioning
confidence: 76%
“…At 16 h, 4HR induced overexpression of RANKL (osteoclast differentiation factor) [29], RUNX2 (a key transcription factor associated with osteoblast differentiation) [30], osterix (a transcription factor for osteoblast differentiation) [31], aggrecan (a cartilage-specific proteoglycan core protein) [32], and calmodulin-dependent kinase II (a key regulator of osteoblast differentiation) [33], which co-operatively stimulated osteoblast differentiation. At 24 h, 4HR induced overexpression of BMP-3 (a negative regulator for bone density) [34], OPG (a regulator for bone density) [35], osteocalcin (a calcium-binding protein) [36], and osteopontin (bone sialoprotein I) [37], which simultaneously regulated osteoid matrix deposition. These results corresponded with those of the Western blot (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when Coco was silenced in 4T1 breast cancer cells that were inoculated via intracardiac injection into mice, no change was seen in cancer cell growth or lesion formation in bone [ 162 ]. These results are intriguing, given that BMP levels are typically high in bone, and BMPs (especially BMP-2) are required for osteoblast differentiation [ 163 , 164 ]. To further explore this result, the authors examined bone production of phospho-Sma-And Mad-Related Protein (also known as phospho-Mothers Against Decapentaplegic Homolog, or phospho-SMAD), a factor in the BMP-2/Smad signaling pathway [ 165 ].…”
Section: Dormant Cancer Cell Re-activation In Bonementioning
confidence: 99%
“…In years since the first description of the ‘vicious cycle’, several groups have added additional components to the classical model. Among them, Sethi et al demonstrated that Jagged1, as expressed on tumor cells, can interact with both osteoblasts and pre-osteoclasts in the bone niche to further drive sustained bone resorption [ 163 ]. Specifically, Jagged1 was shown to bind to the receptor Notch on osteoblasts, leading to signaling through Rbpj and Hey1, and subsequent increased expression of osteoblast-derived IL-6 [ 60 ].…”
Section: The ‘Vicious Cycle’ Of Cancer Metastasis To Bonementioning
confidence: 99%